The Routine Tradition of Reciting the Yellow (Kitab Kuning) Islamic Book in the Menara Kudus in an Ethnographic Perspective: Exploration of Practices, Values, and Meanings for Local Communities - Imaniar Purbasari; Melvia Malva Meirina; David Ferdiansyah; Imma Nikamtul Aliyya; Rizki Arjuna Hidayawan; Nihayatus Sa’adah; Nadya Annatasya (STKIP Taman Siswa Bima, 2025)
The routine tradition of reciting Kitab Kuning at Menara Kudus represents the locality of Kudus which is starting to be faced with the limited involvement of the younger generation in the modern era. This study aims to analyze the implementation the tradition, examine the values of tradition and reveal the meaning of tradition in sustainability. This tradition is carried out at the Menara Kudus Mosque regularly to study the value of life in an Islamic perspective by all social circles. This research uses an ethnographic approach. The implementation of the research involved the community, students, and religious leaders. Observations in the routine recitation activities were carried out to explore the relationship between the meaning of values and the social behavior of the community towards tradition. Interviews were conducted to find the spiritual, social and cultural background that applies in the development of traditions. Documentation was used to support data on cultural and spiritual interrelationships during the recurring implementation of the tradition. Various data sources were used to explore practices, values and meanings for generalization. The results showed that the practical exploration of the routine activities of reciting the book was carried out with simple methods and Javanese language with clear and firm religious meaning as the basis of social life. Religious values provide an understanding of the concept of spirituality to build morals that are in line with social and cultural values. The meaning of the study in the development of knowledge and social ethics is a basic need that cannot be ignored.